1980
DOI: 10.1111/j.1365-2672.1980.tb01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Concentrations of Carbon Dioxide on Growth Rate of Pseudomonas fragi, Bacillus cereus and Streptococcus cremoris

Abstract: The maximum specific growth rates of Pseudomonas fragi, Bacillus cereus and Streptococcus cremoris were studied over a wide range of carbon dioxide concentrations. The growth rate compared with a control was reduced to 50% in Ps. fragiat 0.5 atm C02, in B. cereus at 1.3 atm and in Strep. cremoris at 8.6 atm. B. cereus and Strep. cremoris were completely inhibited at 3 and 11 atm C02, respectively. The growth rate of the aerobic Ps. fragi at 0.99 atm C02 (0.01 atm oxygen) was reduced to about 20% of that in air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 13 publications
5
45
0
2
Order By: Relevance
“…Optical density (600nm) confirmed that biomass density remained near peak levels throughout the experiment (Fig.12B). CO 2 cultures but not N 2 cultures, revealed a 24-hour lag before growth and this is consistent with previously observed dynamics of growth under CO 2 (Enfors and Molin, 1980). While this apparent lag was not observed in the second growth curve experiment, these early dynamics were confounded by a brief intrusion of oxidative potential as evidenced by emergence of a slight pink color in the resazurin dye of sealed cultures from time point 0 to 7 hours in N 2 and CO 2 samples.…”
Section: B Physiological Characterization Of B Cereus Strain Mit0214supporting
confidence: 74%
“…Optical density (600nm) confirmed that biomass density remained near peak levels throughout the experiment (Fig.12B). CO 2 cultures but not N 2 cultures, revealed a 24-hour lag before growth and this is consistent with previously observed dynamics of growth under CO 2 (Enfors and Molin, 1980). While this apparent lag was not observed in the second growth curve experiment, these early dynamics were confounded by a brief intrusion of oxidative potential as evidenced by emergence of a slight pink color in the resazurin dye of sealed cultures from time point 0 to 7 hours in N 2 and CO 2 samples.…”
Section: B Physiological Characterization Of B Cereus Strain Mit0214supporting
confidence: 74%
“…Figure 3 shows an example of a growth curve for growth at optimal conditions, namely, pH 7. The derived max value (2.6 h Ϫ1 ) fits within the range of 2.3 h Ϫ1 to 3.33 h Ϫ1 from published data for growth in laboratory media (10,19). Both OD methods tested, the RRD method and the 2FD method, derived similar max values from the TTD data, so these alternative methods to classic plate counting could confidently be used.…”
Section: Discussionmentioning
confidence: 87%
“…It is also noteworthy that PAO1 showed at least twofold decrease in growth rate and maximum yield at elevated CO 2 . Based on sensitivity to CO 2 , heterotrophs range from those whose growth requires CO 2 under low CO 2 conditions (Kusian et al, 2002;Brown & Howitt, 1969;Bury-Moné et al, 2008;Kempner & Schlayer, 1942;Merlin et al, 2003) to those whose growth is inhibited by elevated CO 2 (Enfors & Molin, 1980;Gill & Tan, 1979), including organisms like P. aeruginosa that may exhibit both characteristics. In the former case, the need for CO 2 is attributed to CO 2 fixation in biosynthetic reactions, and CAs, as discussed above, are shown to be commonly required for survival of these organisms at low levels of CO 2 (Kusian et al, 2002;Burghout et al, 2010;Hashimoto & Kato, 2003;Merlin et al, 2003).…”
Section: Psca1 Psca2 and Psca3 Are Functionally Active Casmentioning
confidence: 99%